2017
DOI: 10.1186/s41065-017-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

SSR marker variations in Brassica species provide insight into the origin and evolution of Brassica amphidiploids

Abstract: BackgroundOilseed Brassica represents an important group of oilseed crops with a long history of evolution and cultivation. To understand the origin and evolution of Brassica amphidiploids, simple sequence repeat (SSR) markers were used to unravel genetic variations in three diploids and three amphidiploid Brassica species of U’s triangle along with Eruca sativa as an outlier.ResultsOf 124 Brassica-derived SSR loci assayed, 100% cross-transferability was obtained for B. juncea and three subspecies of B. rapa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 25 publications
2
35
0
1
Order By: Relevance
“…The frequent mutations in SSR regions are easily to alter the number of repeats, result in a higher degree of polymorphism. Because of these characteristics, SSRs have become important molecular markers for a wide range of applications [43,44]. In compliance with other similar studies [32,45], we detected the perfect SSRs longer than 8 bp because SSRs of 8 bp or longer are prone to slip-strand mispairing, which is thought to be the primary mutational mechanism causing their high level of polymorphism.…”
Section: Repeat Sequence Analysis Of N Cadamba Chloroplast Genomesupporting
confidence: 88%
“…The frequent mutations in SSR regions are easily to alter the number of repeats, result in a higher degree of polymorphism. Because of these characteristics, SSRs have become important molecular markers for a wide range of applications [43,44]. In compliance with other similar studies [32,45], we detected the perfect SSRs longer than 8 bp because SSRs of 8 bp or longer are prone to slip-strand mispairing, which is thought to be the primary mutational mechanism causing their high level of polymorphism.…”
Section: Repeat Sequence Analysis Of N Cadamba Chloroplast Genomesupporting
confidence: 88%
“…In our knowledge, there are no specific molecular markers developed for other related species in the Sesamum genus. It has been demonstrated that SSR markers have a good transferability between species of the same genus or even in the same taxa ( Fan et al, 2013 ; Buso et al, 2016 ; Huang et al, 2016 ; Thakur et al, 2017 ). In sesame, Uncu et al (2015) uncovered a high rate of SSR marker transferability between the cultivated species S. indicum and the proposed wild ancestor species S. malabaricum .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the need of understanding the B. oleracea gene pool for seed yield heterosis in B. napus canola hybrid. It has also been reported that genetic diversity in the C genome is lower than the A genome of B. napus (Bus et al, 2011;Delourme et al, 2013;Thakur et al, 2018); this enforce the need of increasing genetic diversity in the C genome of B. napus by introducing allelic diversity from B. oleracea-not only for increasing the level of heterosis in B. napus hybrid canola but also for continued improvement of the germplasm of this crop through breeding.…”
Section: Introductionmentioning
confidence: 99%